Development a decision support system for selection healthcare chatbot - Phooriyaphan, Sirirak; Rachsiriwatcharabul, Natworapol (Bulletin of Electrical Engineering and Informatics, 2025)
It’s an increasing number of healthcare in many countries. Healthcare chatbot can save money, time and meet patient satisfaction. The healthcare would like to select the best or optimal healthcare chatbot but in the real situations, some healthcare may select the healthcare chatbot by own opinions in the organization with several criteria. The purpose of this research is to design and develop a decision support system (DSS) to select healthcare chatbot under the criteria of: i) functionalities; ii) multilingual ability; iii) usability; and iv) security and privacy. According to this research, it can help healthcare to make a reliable decision. The DSS allows users to select the most suitable alternatives of chatbot. The DSS is analyzed by using analytic hierarchy process (AHP). The result show that the DSS was designed to help in complex decision making and show the making decision of decision maker in the reliable and accurate decision. The result found that it is an appropriate technique for using in the DSS to select the suitable healthcare chatbot in accordance with overall criteria effectively including the sensitivity analysis.